Evaluasi Safety Climate di Perusahaan Penyedia Information and Communication Technology Industri Migas - Amri, Zul; Widanarko, Baiduri (FORIKES, 2025)
Occupational safety climate is a crucial factor in creating a safe work environment, particularly in high-risk industries such as the oil and gas industry. The purpose of this study was to evaluate the safety climate at PT X, an information and communication technology service provider in the oil and gas industry. The study employed a quantitative approach, involving 277 respondents. Data were collected using the NOSACQ-50 questionnaire to measure seven dimensions of safety climate. The data were analyzed descriptively, followed by Importance-Performance Map Analysis (IPMA). The analysis showed that the safety climate was generally moderate, but three dimensions with low performance required special attention: fairness of safety management, priority of worker safety, and worker commitment to safety. Furthermore, it was concluded that the safety climate at PT X was generally moderate, requiring improvements in certain dimensions to enhance the overall safety culture.Keywords: safety climate; safety management; worker commitment; oil and gas industry ABSTRAK Iklim keselamatan kerja merupakan salah satu faktor penting dalam menciptakan lingkungan kerja yang aman, terutama di industri dengan risiko tinggi seperti migas. Tujuan penelitian ini adalah mengevaluasi safety climate di PT X sebagai penyedia layanan information and communication technology di industri migas. Penelitian menggunakan pendekatan kuantitatif, yang melibatkan 277 responden. Data dikumpulkan menggunakan kuesioner NOSACQ-50 untuk mengukur tujuh dimensi iklim keselamatan. Data dianalisis secara deskriptif, dilanjutkan dengan Importance-Performance Map Analysis (IPMA). Hasil analisis menunjukkan bahwa iklim keselamatan secara umum berada pada kategori sedang, namun terdapat tiga dimensi dengan kinerja rendah yang memerlukan perhatian khusus yaitu keadilan manajemen keselamatan, prioritas keselamatan pekerja, serta komitmen pekerja terhadap keselamatan kerja. Selanjutnya disimpulkan bahwa secara umum, iklim keselamatan di PT X berada pada tingkat sedang, sehingga memerlukan perbaikan pada dimensi-dimensi tertentu untuk meningkatkan budaya keselamatan secara menyeluruh.Kata kunci: safety climate; manajemen keselamatan; komitmen pekerja; industri migas